Development of a Social Studies Learning Management Model Emphasizing the Selection of Learning Resources Based on Romiszowski’s Approach to Enhance Understanding of Community Identity among Pre-service Social Studies Teachers - Uttaman, Achira; Lertpradit, Jinnawat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
This research aimed to develop a social studies learning management model that emphasized the selection of learning resources based on the concept of Romiszowski, which affected the understanding of community identity of social studies student teachers by using the systematic Research and Development (R&D) method consisting of 4 steps: needs analysis, model design and development, testing in the subject of "Local Studies" with 33 fourth-year students, and evaluation by both experts and students. Romiszowski ’s concept was used to develop a learning management model that enhances the understanding of community identity among social studies student teachers. There were five learning management steps: (1) Purpose issues of interest (2) Planning meeting (3) Carry out (4) Reflective and (5) Speech as steps in organizing learning activities, emphasizing the use of learning resources from real contexts such as temples, community markets, museums, or local people. The research results found that the developed model was most appropriate and effective. It can promote students’ understanding of the community’s roots, develop their analytical skills, and foster a positive attitude towards cultural diversity, while also creating pride in the locality and generating significant satisfaction from learning from real sources. Therefore, this model has the potential to promote social studies teachers as learning designers who are connected to the learners’ contexts and support the development of lifelong learning.